The causal role of gastroesophageal reflux disease in endometriosis: a bidirectional Mendelian randomization study - Shi, Zunlin; Li, Zhi; Wang, Kana; Yang, Fan (Frontiers in Medicine, 2024)
Observational studies have reported an association between gastroesophageal reflux disease (GERD) and endometriosis. We conducted a two-sample and bidirectional Mendelian randomization analysis to determine whether those associations are causal. Two-sample and bidirectional MR analyses were performed using summary statistics from the European Individual Genome-Wide Association Study (GWAS). The inverse variance weighting (IVW) method is used as the main analysis method to evaluate causality. Sensitivity analyses were performed to assess heterogeneity, horizontal versatility, and stability. The results showed no significant causal association between GERD in women with endometriosis in the UK Bank database [ratio (OR) ≈ 0, 95% adjusted interval (CI) 1.0007∼1.0044, P = 0.006] and Finn databases [ratio (OR) = 1.29, 95% adjusted interval (CI) 0.99∼1.67, P = 0.06]. However, when studying the Finn database only for endometriosis, which is confined to the uterus, a significant increase in GERD was limited to the risk of endometriosis in the uterus [ratio (OR) = 1.47, 95% adjusted interval (CI) 1.00∼2.17, P = 0.05]. Sensitivity analysis showed that the results were robust and did not detect multi efficacy or heterogeneity. Meanwhile, reverse MR analysis showed that endometriosis did not increase the risk of GERD. This MR study supports a causal relationship between GERD and an increased risk of endometriosis confined to the uterus. Therefore, patients with gastric esophageal reflux should be treated with gynecological examination to avoid and prevent the development of endometriosis.